Pseudomonas aeruginosa flagellum is critical for invasion, cutaneous persistence and induction of inflammatory response of skin epidermis. Issue 1 (31st December 2018) - Garcia, Magali; Morello, Eric; Garnier, Julien; Barrault, Christine; Garnier, Martine; Burucoa, Christophe; Lecron, Jean-Claude; Si-Tahar, Mustapha; Bernard, François-Xavier; Bodet, Charles
ABSTRACT: Pseudomonas aeruginosa, an opportunistic pathogen involved in skin and lung diseases, possesses numerous virulence factors, including type 2 and 3 secretion systems (T2SS and T3SS) and its flagellum, whose functions remain poorly known during cutaneous infection. Using isogenic mutants deleted from genes encoding each or all of these three virulence factors, we investigated their role in induction of inflammatory response and in tissue invasiveness in human primary keratinocytes and reconstructed epidermis. Our results showed that flagellum, but not T2SS and T3SS, is involved in induction of a large panel of cytokine, chemokine, and antimicrobial peptide (AMP) mRNA in the infected keratinocytes. Chemokine secretion and AMP tissular production were also dependent on the presence of the bacterial flagellum. This pro-inflammatory effect was significantly reduced in keratinocytes infected in presence of anti-toll-like receptor 5 (TLR5) neutralizing antibody. Bacterial invasion of human epidermis and persistence in a mouse model of sub-cutaneous infection were dependent on the P. aeruginosa flagellum. We demonstrated that flagellum constitutes the main virulence factor of P. aeruginosa involved not only in early induction of the epidermis inflammatory response but also in bacterial invasion and cutaneous persistence. P. aeruginosa is mainly sensed by TLR5 during the early innate immune response of human primary keratinocytes.